Importance of the Sequence-Directed DNA Shape for Specific Binding Site Recognition by the Estrogen-Related Receptor - Mohideen-Abdul, Kareem; Tazibt, Karima; Bourguet, Maxime; Hazemann, Isabelle; Lebars, Isabelle; Takacs, Maria; Cianférani, Sarah; Klaholz, Bruno P.; Moras, Dino; Billas, Isabelle M. L. (Frontiers in Endocrinology, 2017)
Most nuclear receptors (NRs) bind DNA as dimers, either as hetero- or as homodimers on DNA sequences organized as two half-sites with specific orientation and spacing. The dimerization of NRs on their cognate response elements (REs) involves specific protein-DNA and protein-protein interactions. The estrogen-related receptor (ERR) belongs to the steroid hormone nuclear receptor (SHR) family and shares strong similarity in its DNA binding domain (DBD) with that of the estrogen receptor (ER). In vitro, ERR binds with high affinity inverted repeat REs with a 3 bps spacing (IR3), but in vivo, it preferentially binds to single half-site REs extended at the 5’-end by three base pairs (ERREs), thus explaining why ERR was often inferred as a purely monomeric receptor. Since its C-terminal ligand-binding domain is known to homodimerize with a strong dimer interface, we investigated the binding behavior of the isolated DBDs to different response elements using electrophoretic migration, multi-angle static laser light scattering (MALLS), non-denaturing mass spectrometry and nuclear magnetic resonance (NMR). In contrast to ER DBD, ERR DBD binds as a monomer to EREs (IR3), such as the tff1 ERE-IR3, but we identified a DNA sequence composed of an extended half-site embedded within an IR3 element (embedded ERRE/IR3), where stable dimer binding is observed. Using a series of chimera and mutant DNA sequences of ERREs and IR3 REs we have found the key determinants for the binding of ERR DBD as a dimer. Our results suggest that the sequence-directed DNA shape is more important than the exact nucleotide sequence for the binding of ERR DBD to DNA as a dimer. Our work underlines the importance of the shape-driven DNA readout mechanisms based on minor groove recognition and electrostatic potential. These conclusions may apply not only to ERR, but also to other members of the steroid hormone receptor (SHR) family, such as AR or GR, for which a strong well conserved half-site is followed by a weaker one with degenerated sequence.